Quality of the particleboards on Serbian market in regard to the formaldehyde emission - Momčilović Milanka Điporovic; Mlađan Popović; Jasmina Popović; Grmuša Ivana Gavrilović; Fadhil Hamid; Mohamad Ahmad Hakky (Zaštita Materijala)
The formaldehyde potential of particleboards imported on Serbian market was evaluated in this research. The sampling and testing of particleboards were conducted in two discrete periods: first was during 2011 and the second was in the period of 2015-2016. For both periods, the samples of raw particleboards originated from three different producers. The perforator method (EN 120) was used to test the formaldehyde content in the particleboard samples. In general, the results have showed that the majority of the samples belong to the E1 class of particleboards. In addition, 19 % of the particleboards sampled in 2011 and 31 % of the boards sampled in 2015-2016 were found to have formaldehyde content below 50 % of E1 class requirements.